2016
DOI: 10.1186/s12943-016-0510-x
|View full text |Cite
|
Sign up to set email alerts
|

ITGA6 is directly regulated by hypoxia-inducible factors and enriches for cancer stem cell activity and invasion in metastatic breast cancer models

Abstract: BackgroundHypoxia-inducible factors (HIFs) are well-established mediators of tumor growth, the epithelial to mesenchymal transition (EMT) and metastasis. In several types of solid tumors, including breast cancers, the HIFs play a critical role in maintaining cancer stem cell (CSC) activity. Thus, we hypothesized that HIFs may also regulate transcription of markers of breast CSC activity. One approach to enrich for breast cells with stem-like phenotypes is FACS sorting, in which sub-populations of live cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 79 publications
11
108
0
Order By: Relevance
“…Consistent with our results, ITGA6 overexpression was observed in esophageal cancer [48] and colon cancer, [49] and it not only mediates interaction with the ECM but also drives intracellular signaling events that communicate from the tumor microenvironment to inside of the tumor cell to alter phenotypes including migration and invasion. [50] The associations of the ITGA6 with prognosis in cancer is poorly known, with limited studies reporting that this gene affects the prognosis of prostate cancer by influencing the biological characteristics of CSC, [51] and its high expression exhibited significantly poorer OS, [52] which is consistent with our finding in ovarian cancer (Fig. 5).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results, ITGA6 overexpression was observed in esophageal cancer [48] and colon cancer, [49] and it not only mediates interaction with the ECM but also drives intracellular signaling events that communicate from the tumor microenvironment to inside of the tumor cell to alter phenotypes including migration and invasion. [50] The associations of the ITGA6 with prognosis in cancer is poorly known, with limited studies reporting that this gene affects the prognosis of prostate cancer by influencing the biological characteristics of CSC, [51] and its high expression exhibited significantly poorer OS, [52] which is consistent with our finding in ovarian cancer (Fig. 5).…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported, silencing of ITGA6 genes significantly inhibited cell migration and invasion in head and neck cancer cells and hepatocellular carcinoma cells 21,22. Similarly high ITGA6 expression was shown to enhance invasion in models of metastatic breast cancer 23. Moreover, Kwon et al24 found ITGA6 is a possible target for antibody-related diagnostic and therapeutic modalities in esophageal squamous cell carcinoma.…”
Section: Resultsmentioning
confidence: 60%
“…Once in the nucleus, these factors can bind to hypoxia response elements (HREs) and regulate at least transcription of 70 different genes [179]. On one side, this leads to an upregulation of specific integrins such as αvβ3 and the β1 and α6 integrin subunits, which mediate the invasive phenotype of tumor cells [180,181,182]. Moreover, a recent study revealed that HIF-1α activates ILK transcription and that the activation of this kinase stimulates HIF-1α expression via the mTOR pathway, creating a sustained feedback loop that promotes EMT [183].…”
Section: Hallmarking Cancermentioning
confidence: 99%